PERBANDINGAN MODEL PEMBELAJARAN CONCEPT SENTENCE DENGAN COMPLETTE SENTENCE DITINJAU DARI HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU - Sahamudin, Sahamudin; Tamba, Wayan; Kurniawati, Wiwien (Jurnal Ilmiah IKIP Mataram, 2019)
The use of learning models in the teaching and learning process especially in Integrated Social Studies subjects is still lacking, until now it still uses conventional methods (lectures, discussions, and question and answer) so that the lack of learning outcomes. therefore, a learning model is needed that can make students play an active role in learning. then the formulation of the problem is whether there is a Difference in Learning Model Concept Sentence with Complete Sentence Against Student Learning Outcomes in Class VII Integrated Social Sciences Subjects at MTsN 4 Lombok Tengah 2018/2019 Academic Year? .. The purpose of this study is to find out differences in learning outcomes between students using Concept Sentence Learning Model with those using the Complete Sentence Model on Class VII Integrated Social Sciences subjects at MTsN 4 Lombok Central Academic Year 2018/2019. The method used in this study is an experimental method with a Two Group Posttest Design research design, where class VII A uses Concept sentence, while class VII B uses Complete Sentence. The study sample totaled 21 people in class VII A and 21 people in class VII B, from 85 populations consisting of 3 classes. Data collection techniques in this study used the test method as the principal method, observation method and documentation as a complementary method. The data analysis technique uses the T-test formula. The results of the analysis show that from the results of tcount = 3.385 with n db = n_1 + n_2 - 2 = 21 + 21 - 2 = 40 and a significant level of 5%, then ttable = 2.021 shows that tcount â‰¥ ttabel so Ho is rejected and H1 is accepted. From these results it can be concluded that there are significant differences between the two Concept Sentence learning models with Complette Sentence Against Student Learning Outcomes in VII grade Integrated Social Studies subjects at MTsN 4 Lombok Central Academic Year 2018/2019. This is evident from the results of the tcount greater than ttabel1 (3.385> 2.021). Means the results of this study are significant.